1995
DOI: 10.3109/00016349509009946
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial adenocarcinoma with clinical evidence of cervical involvement: Accuracy of diagnostic procedures, clinical course, and prognostic factors

Abstract: The only relevant staging procedure is the histological examination of cervix without the preoperative irradiation. According to our results it seems that simple hysterectomy instead of radical (Wertheim operation) hysterectomy may be a sufficient operative treatment of stage II endometrial carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 25 publications
2
47
0
2
Order By: Relevance
“…Negative and positive predictive values of the ECC procedure varied between (87.5%-98.3%) and (15.1%-62.5%) in previous studies [7,10,12,23,25]. These differences can partly be explained by heterogeneity in patient selection and differences in assessment of the curettage.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…Negative and positive predictive values of the ECC procedure varied between (87.5%-98.3%) and (15.1%-62.5%) in previous studies [7,10,12,23,25]. These differences can partly be explained by heterogeneity in patient selection and differences in assessment of the curettage.…”
Section: Discussionmentioning
confidence: 81%
“…Numerous studies reported the value of other preoperative staging procedures in diagnosing cervical involvement, such as cervical cytology [7,10,12,22], CT scan [23], transvaginal ultrasonography [12,23] and MRI [23,24]. Cervical cytology, CT and transvaginal ultrasonography showed poor results and are not suitable for detecting cervical involvement [7,10,12,22,23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another report analyzing overall survival (OS) in stage II endometrial cancer patients showed that there was no survival benefit in patients treated with RH compared with those treated with TAH [15]. Additionally, a prospective randomized study showed that mRH did not reduce locoregional recurrence [16]. So, the extent of hysterectomy has not been determined in early-stage endometrial cancers.…”
Section: Introductionmentioning
confidence: 99%